Association of domain-specific physical activity with nocturia: a population-based study - Yangtao Jia; Rui Shen; Xinke Dong; Fangzheng Yang; Libin Zhou; Huimin Long (Scientific Reports)
Abstract Nocturia is the most prevalent lower urinary tract symptom (LUTS) and is closely associated with various diseases and social burdens. Research on the relationship between physical activity and various diseases has progressed significantly. However, the association between nocturia and physical activity has received limited attention in prior studies. Thus, this study aimed to investigate the relationship between different domains of physical activity (e.g., occupation-related physical activity [OPA], transportation-related physical activity [TPA], and leisure-time physical activity [LTPA]) and nocturia. We included 5516 participants from the cross-sectional National Health and Nutrition Examination Survey (NHANES) conducted between 2007 and 2012, employing survey-weighted logistic regression, restricted cubic splines (RCS), subgroup analysis, and sensitivity analysis to assess the relationship between different domains of physical activity and nocturia. Multivariable logistic regression analysis revealed a significant negative correlation between PA, LTPA, and nocturia. Specifically, PA (OR 0.7523, 95% CI 0.6307–0.8974, P = 0.002) and LTPA (OR 0.7664, 95% CI 0.6314–0.9304, P = 0.007) were negatively associated with nocturia. The RCS curve demonstrated non-linear relationships between PA, LTPA, and nocturia. Additionally, subgroup analyses and sensitivity analyses further validated this association. Based on this cross-sectional study, we suggested that PA and LTPA are associated with a reduced risk of nocturia in adults aged 20 years and older in the United States. This underscores the importance of physical activity in preventing and managing nocturia may provide valuable guidance for clinical practice.